THE EFFECT OF WORKING CAPITAL, SOLVABILITY AND LIQUIDITY ON PROFITABILITY IN INFRASTRUCTURE, TRANSPORTATION, AND UTILITY - Nainggolan, Desi May Sari; Nathalia, Christine; Tarigan, Hestia Amalia Br; Siburian, Peronika; Sinaga, Jholant Bringg Luck Amelia Br (2020)
This study aims to determine the effect of working capital, solvency and liquidity partially or simultaneously significantly influence the profitability of infrastructure, transportation and utility companies listed on the Indonesia stock exchange period 2015-2017. The method used in this research is a quantitative approach, the type of descriptive research, the nature of explanatory research, with documentation data collection techniques, the type of data used is secondary data. The population used was 38 companies and a sample of 57. The classic assumption tests used were the normality test, the multicollinearity test, the autocorrelation test, the heteroscedasticity test. The coefficient of determination test results indicate working capital,solvency and liquidity to profitability of 16.5% while the remaining 83.5% other variables examined by this study, such as debt to equity ratio, quick ratio and other ratios. Where working capital in this study calculations using net working capital (net workingcapital), solvency calculations using debt to assets ratio, liquidity calculations using currentratios, and profitability calculations using return of assets. The research results partially working capital affect profitability. The results of the study partially working capital affect profitability, solvency partially does not affect profitability, and partial liquidity does not affect profitability.